2018
DOI: 10.1097/won.0000000000000455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyhexamethylene Biguanide Solution on Bacterial Load and Biofilm in Venous Leg Ulcers

Abstract: The results of this study indicate that both PHMB and saline solution are effective in reducing the bacterial load in venous leg ulcers. However, bacterial biofilm was present after cleansing with both solutions. These findings provide important evidence regarding effectiveness of 2 common wound cleansers on bacterial presence in wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Regarding the reduction of bacterial load, in order to minimize critical colonization and possible infection, the importance of a careful cleaning of the wound is highlighted. It can be done using physiological solutions or composed of antimicrobials such as polyhexamethylene biguanide (PHMB); and, when available under pressure, in the form of a jet (43) , it helps to minimize the risk of infection.…”
Section: Descriptive N = 126 Culture and Antibiogrammentioning
confidence: 99%
“…Regarding the reduction of bacterial load, in order to minimize critical colonization and possible infection, the importance of a careful cleaning of the wound is highlighted. It can be done using physiological solutions or composed of antimicrobials such as polyhexamethylene biguanide (PHMB); and, when available under pressure, in the form of a jet (43) , it helps to minimize the risk of infection.…”
Section: Descriptive N = 126 Culture and Antibiogrammentioning
confidence: 99%
“…In addition, comparable efficacy of PHMB to chlorhexidine (CHG) was demonstrated against P aeruginosa biofilm grown in routinely used microtitre plates and on silicone materials in vitro in artificial wound fluid 96 . However, although PHMB was equally as effective as saline solution in reducing the bacterial load in venous leg ulcers, neither treatment was able to eliminate biofilm from the wound tissue 97 . Furthermore, conflicting evidence exists regarding the activity of PHMB against S aureus biofilms 98,99 …”
Section: Resultsmentioning
confidence: 99%
“…96 However, although PHMB was equally as effective as saline solution in reducing the bacterial load in venous leg ulcers, neither treatment was able to eliminate biofilm from the wound tissue. 97 Furthermore, conflicting evidence exists regarding the activity of PHMB against S aureus biofilms. 98,99…”
Section: Polyhexanidementioning
confidence: 99%
“…10 The comparators • In an RCT conducted in venous leg ulcers (VLUs, n= 27 analysed) that had biofilm presence confirmed by microscopy, cleansing with a PHMB-iodine solution statistically significantly reduced overall bacterial count compared to baseline, but this was not significantly different from saline cleansing (p > 0.05). There was a statistically significantly greater reduction in bacterial count in relation to wound size in the PHMB-iodine group (p = 0.07) 11 (Level 1).…”
Section: Clinical Evidence Reduction In Local Infectionmentioning
confidence: 87%
“…of RCTs and other study designs 23 1.c RCT 11,14 Level 2.c Quasiexperimental prospectively controlled study 12 Level 3.e Observational study without a control group 15 4.c Case series 19 4.d Case studies [16][17][18]24 5.a Systematic review of expert opinion 25 5.b Expert consensus 13,26,27 5.c Bench research [1][2][3][4][5][6][7][8][9] and single expert opinion literature search combining search terms related to PHMB and wounds. Only studies that reported on the use of PHMB for a chronic wound were included in the clinical evidence summary.…”
Section: B Systematic Reviewmentioning
confidence: 99%